Application of Waterfall Method in Development of Tourism Bike-Sharing Transaction Information System at JojgaBike - Mabruri, Rifqi Tri; Wibawa, Wibawa; Wardana, Ari Kusuma; Setyorini, Arifah Indah (Fakultas Teknik Universitas Muria Kudus, 2024)
JogjaBike is one of the tour bike-sharing service companies. The problem with JogjaBike is related to the lack of activities that educate customers about the flow of the rental transaction system. The tourism bike-sharing transaction information system that is implemented is still managed conventionally. Referring to the problems with JogjaBike, the purpose of this research is to design a website-based rental transaction information system at JogjaBike. The modeling used to develop information systems is the waterfall method. The results show that the system can run as expected. In addition, usability testing results with a value is 84.29 included in the NPS